Indonesia Poverty Reduction Strategies: Shifting policies to promote employment in the poorest four deciles - Ardi Adji; Sri Hartini Rachmad (Institute for Economic and Social Research, 2017)
This paper observes the working status and conditions of people who fall into the poorest four deciles in Indonesia. The research aims to provoke policy shifts in the drive to accelerate poverty reduction in Indonesia, taking a longer view of people being more employable and less dependent; also identifying the dominant factors preventing people from moving out of poverty and improving their life quality. By comparing elements of gender, age, education and health against employment status and opportunities. Simultaneously social assistance and protection programs are evaluated in relation to their stated target groups to determine their suitability and their impact.